Ubiquinone Content of Daily Meals - FUJITA, Tadao; OSHIBA, Keiichi; MORISAWA, Seiji; ODACHI, Jyunko; MATSUI, Isao; OTANI, Shuzo; KANBE, Tamotsu; KAMEI, Masaharu; SASAKI, Kiyoshi (Nihon Eiyō, Shokuryō Gakkai shi, 1986)
Since exogenous ubiquinone (UQ) has useful clinical effects, UQ contained in foods might also have some effects. We determined UQ content of daily meals using high performance liquid chromatography. In bread meals, the average contents of UQ-9 and UQ-10 were 0.5mg and 1.4 mg, respectively. As bread and milk in bread meals contained 0.18 of UQ-9 and 0.14 of UQ-10, almost half of UQ-9 and large amounts of UQ-10 in these meals were found to be supplied from subsidiary foods. The average contents of UQ-9 and UQ-10 in rice meals were 0.4mg and 2.4mg, respectively. A considerable amount of UQ-9 was supplied from rice, however, almost all UQ-10 was derived from subsidiary foods in rice meals. The sources of UQ-10 found in this study were fishes, meats and vegetable oils. Since the daily UQ intake derived from meals was 1.2-1.5mg of UQ-9 and 4.2-7.2mg of UQ-10, total intake of UQ-9 and UQ-10 were 19-32% of ordinary amounts admistered clinically. UQ in meals is supplied to the body everyday might have some physiological effects.